Tout est-il colonial dans le Maghreb ? Ce que les travaux des historiens modernistes peuvent apporter - Isabelle Grangaud; M’hamed Oualdi (L’Année du Maghreb)
The colonial history of North Africa, because of its violence and because of the huge transformations it caused within North African societies, shaped a vision of the past that obscured other historical processes far more deeply rooted than colonial processes. This paper not only aims at emphasizing the impact of these other, deeper historical processes, it also suggests that by taking into account this "longue durée", we should reconsider the analytical frameworks and our broad understanding of Maghreb history in general and its colonial history in particular. The first section of the paper analyzes the outlines of the colonial history; it examines the limitations of the spatial framework and the timeline markers used within this field of research. The second section examines the new vistas of research opened through serious consideration of the legacy and persistent effects of early modern history in North Africa. It explores these new perspectives in terms of time and space and our interpretations of North African primary sources.